Knee Osteoarthritis: Kinesiophobia and Isometric Strength of Quadriceps in Women - Saulo Machado; null Érika Santana; Victor Brito; Leonardo Maciel; Lucindo J. Quintans Júnior; Walderi da Silva Junior; Jader de Farias Neto; Henrique Douglas Melo Coutinho; Bonglee Kim; Valter J. de Santana Filho (Pain Research and Management)
Introduction. Osteoarthritis is a disease characterized by progressive wear and tear of the joint, with the knee being the most affected region. These patients have reduced mobility and mobility, among other symptoms. Thus, it is necessary to know the variables that influence the ability to walk. Objective. To analyze how much the gait capacity, in the performance of the six-minute walk test, can be influenced by the maximum isometric strength of the quadriceps or by kinesiophobia in women with knee osteoarthritis. Materials and Methods. This is a cross-sectional study with a sample of 49 women diagnosed with osteoarthritis. The evaluation was carried out in a single moment. Variables studied isometric quadriceps strength, level of fear of movement (kinesiophobia), and ability to walk. Simple linear regression analyzes were performed, with gait ability as the dependent variable and maximum isometric strength and kinesiophobia as independent. Data were presented with mean and standard deviation and were analyzed by the SPSS Statistic 22.0 software, considering p<0.05 as significant. Results. The maximum isometric strength presents a significant difference, directly interfering with the gait ability; as kinesiophobia does not show a statistically significant difference, it does not directly interfere with the ability to walk. Conclusion. Maximal quadriceps isometric strength directly interferes with gait ability in women with knee osteoarthritis, thus suggesting the inclusion of this strategy in treatment programs for this population.